Tumor necrosis factor receptor‐associated factor 5 is an essential mediator of ischemic brain infarction. (19th March 2013) - Wang, Lang; Lu, Yanyun; Guan, Hongjing; Jiang, Dingsheng; Guan, Yu; Zhang, Xin; Nakano, Hiroyasu; Zhou, Yan; Zhang, Yan; Yang, Li; Li, Hongliang
Abstract: Tumor necrosis factor receptor‐associated factor 5 (TRAF5) is an adaptor protein of the tumor necrosis factor (TNF) receptor superfamily and the interleukin‐1 receptor/Toll‐like receptor superfamily and plays important roles in regulating multiple signaling pathways. This study was conducted to investigate the role of TRAF5 in the context of brain ischemia/reperfusion (I/R) injury. Transient occlusion of the middle cerebral artery was performed on TRAF5 knockout mice (KO), neuron‐specific TRAF5 transgene (TG), and the appropriate controls. Compared with the WT mice, the TRAF5 KO mice showed lower infarct volumes and better outcomes in the neurological tests. A low neuronal apoptosis level, an attenuated blood‐brain barrier (BBB) disruption and an inhibited inflammatory response were exhibited in TRAF5 KO mice. TRAF5 TG mice exhibited an opposite phenotype. Moreover, the Akt/FoxO1 signaling pathway was enhanced in the ischemic brains of the TRAF5 KO mice. These results provide the first demonstration that TRAF5 is a critical mediator of I/R injury in an experimental stroke model. The Akt /FoxO1 signaling pathway probably plays an important role in the biological function of TRAF5 in this model. Abstract : In this study, we demonstrated that TRAF5 deficiency leads to inhibited inflammation, BBB disruption and neuronal apoptosis in the ischemic brain probably via the suppression of NF‐κB signaling and the activation of Akt/FoxO1 signaling. Neuron‐specific TRAF5 transgenic mice showed an opposite phenotype which confirmed the findings.